Jaw myology and bite force of the monk parakeet (Aves, Psittaciformes) - Carril, Julieta (2015)
Psittaciform birds exhibit novelties in jaw bone structure and musculature that are associated with strong bite forces. These features include an ossified arcus suborbitalis and the muscles ethmomandibularis and pseudomasseter. We analyse the jaw musculature of the monk parakeet (Myiopsitta monachus) to enable future studies aimed at understanding craniofacial development, morphology, function and evolution. We estimate bite force based on muscle dissections, physiological cross-sectional area and skull biomechanical modelling. We also compare our results with available data for other birds and traced the evolutionary origin of the three novel diagnostic traits. Our results indicate that, in Myiopsitta, (i) the arcus suborbitalis is absent and the orbit is ventrally closed by an elongate processus orbitalis and a short ligamentum suborbitale; (ii) the ethmomandibularis muscle is a conspicuous muscle with two bellies, with its origin on the anterior portion of the septum interorbitale and insertion on the medial aspect of the mandible; (iii) the pseudomasseter muscle consists of some fibers arising from the m. adductor mandibulae externus superficialis, covering the lateral surface of the arcus jugalis and attaches by an aponeurotic sheet on the processus orbitalis; (iv) a well-developed adductor mandibulae complex is present; (v) the bite force estimation relative to body mass is higher than that calculated for other non-psittaciform species; and (vi) character evolution analysis revealed that the absence of the arcus suborbitalis and the presence of the m. pseudomassseter are the ancestral conditions, and mapping is inconclusive about presence of one or two bellies of the m. ethmomandibularis.